Analisis Nilai Relevansi Pengungkapan Corporate Social Responsibility Dengan Diversitas Direksi Sebagai Variabel Moderasi - Diajeng Fitri Wulan; Lindrianasari Lindrianasari; Yunia Amelia; Rindu Rika Gamayuni (Universitas Muhammadiyah Malang, 2022)
This study aims to see the value relevance ​​of CSR Disclosure. The object of this research is all companies listed on the IDX in 2020 which publish an annual report with 352 observation companies. The data used is taken from the company’s annual report by using purposive sampling. This study examines the effect of CSR Disclosure on value relevance with board diversity (gender, age, and education) as the moderating variable. By using statistical descriptive tests and regression analysis, it is ensured that CSR Disclosure does not affect the value of relevance, meaning that it does not affect the reactions and considerations of investors’ decisions. The moderating variable also cannot provide a significant influence on CSR Disclosure and its effect on the value relevance. This is because of investors’ considerations that are still focused on the company’s financial performance compared to the company’s non-financial performance companies. The contribution of this research can be used as reference in decisions and policies in the company’s annual reporting to influence market reactions to information disclosure. In addition, it can also be used as a reference for the regulators to pay more attention to the CSR disclosure of the companies to be more thorough.